Single-cell genomics-based analysis reveals a vital ecological role of Thiocapsa sp. LSW in the meromictic Lake Shunet, Siberia. Issue 12 (3rd December 2021) - Wu, Yu-Ting; Chiang, Pei-Wen; Tandon, Kshitij; Rogozin, Denis Yu; Degermendzhy, Andrey G.; Tang, Sen-Lin
Abstract : Meromictic lakes usually harbour certain prevailing anoxygenic phototrophic bacteria in their anoxic zone, such as the purple sulfur bacterium (PSB) Thiocapsa sp. LSW (hereafter LSW) in Lake Shunet, Siberia. PSBs have been suggested to play a vital role in carbon, nitrogen and sulfur cycling at the oxic–anoxic interface of stratified lakes; however, the ecological significance of PSBs in the lake remains poorly understood. In this study, we explored the potential ecological role of LSW using a deep-sequencing analysis of single-cell genomics associated with flow cytometry. An approximately 2.7 Mb draft genome was obtained based on the co-assembly of five single-cell genomes. LSW might grow photolithoautotrophically and could play putative roles not only as a carbon fixer and diazotroph, but also as a sulfate reducer/oxidizer in the lake. This study provides insights into the potential ecological role of Thiocapsa sp. in meromictic lakes.